2017
DOI: 10.1111/jerd.12353
|View full text |Cite
|
Sign up to set email alerts
|

The impact of silver nanoparticles integration on biofilm formation and mechanical properties of glass ionomer cement

Abstract: As the modification of GIC with silver nanoparticles improved the antibiofilm properties without altering its mechanical properties, it could be used as a restoration of root carious lesion mainly in nonesthetic areas, a base under composite restorations in deep posterior cavities and as a core material in caries susceptible patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 39 publications
(66 reference statements)
2
29
0
Order By: Relevance
“…The addition of nanoparticles in glass ionomer was investigated by many investigators. (15,(33)(34)(35)(36) They tested the biological properties (antibacterial effect), the physical properties as well as the mechanical properties, (49) Dental literature lacks information about the effect of addition of nanoparticles on the final cement colour. In some investigations shear bond strength was tested without the final restorations, which is not the case in this current investigation to try to simulate clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of nanoparticles in glass ionomer was investigated by many investigators. (15,(33)(34)(35)(36) They tested the biological properties (antibacterial effect), the physical properties as well as the mechanical properties, (49) Dental literature lacks information about the effect of addition of nanoparticles on the final cement colour. In some investigations shear bond strength was tested without the final restorations, which is not the case in this current investigation to try to simulate clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive resin cements bond to both tooth structure and restoration. But, due to difficulty in removal of restorations cemented with adhesive resin cements as well as practitioners inevitably remove more tooth structure than needed to remove a bonded resin-cemented lithium disilicate restoration, (33) it appears that luting the lithium disilicate restorations with conventional resin modified glass ionomer or conventional glass ionomer cements to be an acceptable choice when there exists a retentive tooth preparation. It allows less traumatic crown removal when needed.…”
Section: El-wassefy Et Al (2017)mentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its antimicrobial activity and synergizing effects, researchers have studied the use of AgNPs in several areas of dentistry which include dental biomaterials [15][16][17], dental implants [18], orthodontic adhesives [19] etc. In vitro studies have shown, addition of AgNPs in to dental restorative materials inhibit growth of common oral microbes like Streptococcusmutans, Streptococcus sanguinis,and Lactobacillus through bactericidal and bacteriostatic effects of AgNPs on oral microbes [16,20] without altering its mechanical properties [21].…”
Section: Introductionmentioning
confidence: 99%